2007
DOI: 10.1007/s11661-007-9338-8
|View full text |Cite
|
Sign up to set email alerts
|

Incipient Plasticity and Shear Band Formation in Bulk Metallic Glass Studied Using Indentation

Abstract: This study focuses on investigating certain aspects of deformation in bulk metallic glasses (BMGs) based on nanoindentaion and microindentation studies. Using a Berkovich indenter in nanoindentation, the incipient plasticity or early stages of deformation have been studied for a typical BMG, Vitreloy 1. From a critical analysis of the load-displacement curves, the initial displacement burst, often associated with the initiation of shear bands, was found to occur at a value close to the theoretical shear stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…[38] From these data, the theoretical shear strength (s theor ) for the soda-lime-silica glass can be estimated as~6 GPa based on the approximation s theor~G /5. [39] Comparing the estimated values of s max and s theor , it appears that the maximum shear stress generated just below the tip of the Berkovich indenter used in the present work was of the order of or slightly greater than the theoretical shear strength of the soda-lime-silica glass. Therefore, it is plausible to argue that the applied loading provided enough shear stress to cause shear induced flow or deformation in the indented soda-lime-silica glass.…”
Section: Resultsmentioning
confidence: 59%
“…[38] From these data, the theoretical shear strength (s theor ) for the soda-lime-silica glass can be estimated as~6 GPa based on the approximation s theor~G /5. [39] Comparing the estimated values of s max and s theor , it appears that the maximum shear stress generated just below the tip of the Berkovich indenter used in the present work was of the order of or slightly greater than the theoretical shear strength of the soda-lime-silica glass. Therefore, it is plausible to argue that the applied loading provided enough shear stress to cause shear induced flow or deformation in the indented soda-lime-silica glass.…”
Section: Resultsmentioning
confidence: 59%
“…It was found that the hardness of the shear band zone beneath the indentation cavity is smaller than that of the area without deformation because of deformation-induced softening [8]. Some researchers reported that the load-displacement curve (p-h curve) of BMGs during the indentation process exhibits displacement bursts, known as "pop-ins" or "serrations" [9][10][11][12][13][14][15][16][17]. They also observed that the pop-in size varies with indentation depth and indentation loading rate.…”
Section: Introductionmentioning
confidence: 99%
“…This happened because the maximum shear stress (τ max ∼ 14 GPa) calculated following [24] as a function of the effective applied normal force, P eff = P (1 + μ 2 ) 0.5 , increased with scratching speed (Fig. 7f) and its magnitude was much greater than the theoretical shear strength τ theor ∼ 3-6 GPa of SLS glass [20,25,26]. Based on the present experimental evidences, two qualitative models are schematically presented for surface tensile cracks formed and interacted to create a probable zone for micro-chipping, Fig.…”
Section: Resultsmentioning
confidence: 98%